Pengaruh Academic Self-Efficacy terhadap Academic Performance Mahasiswa Angkatan 2021 Universitas Negeri Padang - Yuli Rahmadini; Fadila Lailatul Isttianah; Lidya Yuliani (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
This study aims to determine the effect of academic self-efficacy on academic performance in the 2021 intake of students at Padang State University. Academic self-efficacy is an individual's belief in their ability to complete academic tasks, which is believed to play a significant role in determining student academic achievement. This study used a quantitative approach with a survey method, involving 55 respondents as a sample. Data collection was carried out through a questionnaire using a Likert scale to measure students' academic self-efficacy levels, as well as data collection on their Grade Point Average (GPA) as an indicator of academic performance. Data analysis was carried out using the SPSS program, through several testing stages, namely instrument validity and reliability tests, and simple linear regression tests to determine the effect of independent variables on the dependent variable. The results of the analysis indicate a positive and significant influence between academic self-efficacy and academic performance. This is evidenced by the regression coefficient value of 0.009, with a calculated t-value of 15.278, which is greater than the t-table of 2.266, and a significance value of 0.006, which is less than 0.05. These findings indicate that the higher a student's level of confidence in their academic abilities, the better their academic achievement. Therefore, developing academic self-efficacy can be an important strategy for improving the quality of learning and student academic achievement.